Workshop PTK dan Penulisan Proposal bagi Guru Madrasah Aliyah (MA) Badrul Islam Gulung ulung - Dedi Aprianto; Muhammad Arfa; Sasih Gunalan; Hariono; Bayu Aji Pamungkas (Universitas Lancang Kuning, 2022)
Doing a community service on workshop on the perspectives of Classroom Action Research (CAR) along with writing its proposal towards Islamic Senoir High School’s teachers is based on urgent necessity letting them develop their knowledge on CAR as well as their writing skills of CAR’s proposal. It is worthy that workshop program is considered as an effective imput for the teachers to do CAR as one the parts of those’s instructional responsibility in purpose of improving learning-teaching activities in his/her classroom. CAR must have been as an important problem-solver to make the classroom’s problem up by doing it that it would have yielded the potential methods to undertake an effective classroom’s activities. The methods used used is based on the solution offered, giving the perspectives on CAR along with traning the teachers to write its proposal. This community program suggests that workshop on Classroom Action research was favorably conducted. It was assessed through questionnaires to require the teachers’ perception on workshop activities, namely their perception on knowledge and understanding on the perspectives of CAR 2.9. Furthermore the teachers’ competency on proposal writing activities were assessed 2.8. the assessment was adapted on Likert’s scale (1-4).